2011
DOI: 10.5507/ag.2011.019
|View full text |Cite
|
Sign up to set email alerts
|

School and weekend physical activity of 15-16 year-old Czech, Slovak and Polish adolescents

Abstract: BACKGROUND:When it comes to physical activity, adolescents are the group at the highest risk. When monitoring physical activity in adolescents, it is necessary to diff erentiate school and weekend days. School days are crucial in adolescents' weekly physical activity.OBJECTIVE: The aim of the study is to identify to what extent the school day and weekend physical activity levels diff er in Czech, Polish and Slovak boys and girls with diff erent cultural and education backgrounds in Central Europe. METHODS:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
2
19
0
2
Order By: Relevance
“…Mean daily step count on school days and weekends in less active girls equals 7717 steps/day (6040 steps/day at weekends), and in boys, 7707 steps/day (5821 steps/ day at weekends); these low counts are alarming. Our study confirmed again that girls respond better to wearables than boys [20,43] (e.g. less missing data, interest in use of pedometers after the end of study period) and that the gender-differences in PA volume (as expressed by step counts) have been diminishing.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Mean daily step count on school days and weekends in less active girls equals 7717 steps/day (6040 steps/day at weekends), and in boys, 7707 steps/day (5821 steps/ day at weekends); these low counts are alarming. Our study confirmed again that girls respond better to wearables than boys [20,43] (e.g. less missing data, interest in use of pedometers after the end of study period) and that the gender-differences in PA volume (as expressed by step counts) have been diminishing.…”
Section: Discussionsupporting
confidence: 82%
“…The lowest difference in daily step count between boys and girls with higher and lower PA was found on Mondays; efforts to decrease this difference even further might be especially important as a way to compensate for Sundays, as the most critical day with the lowest level of PA. The low level of PA on Sundays has been previously reported by numerous studies [20,[38][39][40][41]. The unfavourable PA on Sundays in the least physically active adolescents has not been getting any better thus far.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Dílčí výzkumy realizovalo CKV i v Polsku (Frömel, Stelzer, & Groffi k, 2008;Nováková Lokvencová, Frömel, Chmelík, Groffi k, & Bebčáková, 2011). Zvolenou problematiku výzkumu podporují již dříve zjištěná fakta o významu aktivního transportu pro celkovou PA dětí a adolescentů (Cooperet et al, 2003).…”
Section: úVodunclassified
“…Bunc postulates that the decrease has been approximately by 30 % in the past two decades [4]. When comparing working and weekend days, young people do more physical activities during the week, which is probably because of the school physical activities they engage in [5,6,7]. The same conclusion applies also to engaging obese children's involvement in PA [8].…”
Section: Introductionmentioning
confidence: 99%